Faktor Non-Ekonomi dalam Kesuksesan Akademik: Studi Kasus di SMP Negeri 6 Palangka Raya - Puteri Nur Syifa N.A; Tiffany Ramadina P; Laura I.M.F Simanjuntak; Nani Hidayati; Melinda Febriani; M. Hafidz Rahman; Novian Fikri Fadilah; Misnawati Misnawati; Olga Dona Retsi; Linggua Sanjaya Usop; Patrisia Cuesdeyeni (Universitas Palangka Raya, 2025)
This study examines the role of non-economic factors in students' academic success at SMP Negeri 6 Palangka Raya using a qualitative case study approach. The findings indicate that while economic status influences access to learning resources, internal factors such as motivation, interests, and talents play a crucial role in students' achievements. Additionally, family support, a conducive school environment, and positive peer interactions further enhance academic success. Most importantly, students' perseverance and effort prove to be key factors, demonstrating that economic limitations can be overcome with determination and proper support.